The Occurrence Rate of the Fission Illusion Differs Depending on the Complexity of Visual Stimuli - Yasuhiro Takeshima; Jiro Gyoba (i-Perception, 2011)
A fission illusion (also named a double—flash illusion) is a famous phenomenon of audio-visual interaction, in which a single brief flash is perceived as two flashes when presented simultaneously with two brief beeps (Shames, Kamitani, & Shimojo, 2000; 2002). The fission illusion has been investigated using relatively simple visual stimuli like single circle. Thus the illusion has not been examined by using complex visual stimuli. Markovic & Gvozdenovic (2001) reported that the processing of complex visual stimuli tends to be delayed. Therefore, the complexity of visual stimuli may affect the occurrence rate of the fission illusion, since this illusion is generated in the process that copes with visual and auditory stimuli in a short time. The present study examined the differences in illusory occurrence rates by manipulating the complexity of visual stimuli. We used the patterns proposed by Garner & Clement (1963) to control the complexity. The results indicated that it was more difficult to induce the fission illusion by using complex visual stimuli than it was by using simple stimuli. Thus, the present study suggested that the occurrence rate of the fission illusion differed depending on the perceptual efficiency in the coding process of visual stimuli. This study was supported by Grant-in-Aid for Specifically Promoted Research (No. 19001004).